Prioritizing business quality improvement of fresh agri-food SMEs through open innovation to survive the pandemic: A QFD-Based model - Tutur Wicaksono; Md Billal Hossain; Csaba Bálint Illés (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
It is important that SMEs are able to prioritize business quality by identifying business requirements based on customer requirements. This strategy is able to help SMEs generate innovation in the form of improved business quality activities to meet customer requirements. This approach uses the "quality function deployment (QFD)" method to identify the priority business requirements and improvement actions to generate business quality. As a result, we managed to identify five priority variable business requirements (BReqs) based on seven variable customer requirements (CReqs) with the lowest satisfaction score. We proposed some improvement actions in perspective quality based on five priority business requirements. Moreover, the final quality matrix of business quality improvement priority generally makes it easier for users to read and find out which variables need to be improved. This research also presents a solution so that users can perform business actions effectively and efficiently in allocating their resources.
Keywords: 650; SMEs; business quality; QFD; satisfaction; improvement; agri-food